Effects of whole-stream nitrogen enrichment and litter species mixing on litter decomposition and associated fungi - Ferreira, Verónica (2016)
Nutrient enrichment and changes inripariantree species compositionaffectmany streams worldwide but their combined effects on decomposers and litter decomposition have been rarely assessed. In this study we assessed the effects of experimental nitrogen (N) enrichment of a small forest stream on the decomposition of three leaf litter species differing in initial chemical composition [alder (Alnus glutinosa), chestnut (Castanea sativa) and poplar (Populus nigra)], incubated individually and in 2-species mixtures during late spring-early summer. To better understand the effects of litter mixing on litter decomposition, componentlitter species were processed individually for remaining mass and fungal reproductive activity. Litter decomposition rates were high. Nitrogen enrichment significantly stimulated litter decomposition only for alder incubated individually. Differences among litter treatments were found only at the N enriched site where the nutrient rich alder litter decomposed faster than all other litter treatments; only at this site was there a significant relationship between litter decomposition and initial litter N concentration. Decomposition rates of all litter mixtures were lower than those expected from the decomposition rates of the component litter species incubated individually, at the N enriched and reference sites, suggesting antagonistic effects of litter mixing. Conidial production by aquatic hyphomycetes for each sampling date was not affected by nutrient enrichment, litter species or mixing. Aquatic hyphomycetes species richness for each sampling date was higher at the N enriched site than at the reference site and higher for alder litter than for chestnut and poplar, but no effect of mixing was found. Aquatic hyphomycetes communities were structured by litter identity and to a lesser extent by N enrichment, with no effect of mixing. This study suggests that nutrient enrichment and litter quality may not have such strong effects on decomposers and litter decomposition in warmer seasons contrary to what has been reported for autumn-winter. Changes in the composition of the riparian vegetation may have unpredictable effects on litter decomposition independently of streams trophic state